Cosmetic composition containing cellulose and coating powder and having excellent color development
Patent Information
- Application Number
- KR1020230164575
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-11-23
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2043-11-23
Smart Images

Figure 112023131110714-PAT00007_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a cosmetic composition comprising cellulose and a powder surface-treated with at least one coating agent, and to a cosmetic composition that does not contain microplastics and has excellent cosmetic effects such as spreadability, adhesion, and durability. Background Technology
[0002] Microplastics are intentionally manufactured synthetic polymer compounds with a microscopic size of 5 mm or less. Specifically, they refer to solid plastics called microbeads used in cosmetics or detergents. In cosmetic compositions, polymethyl methacrylate (PMMA), polytetrafluoroethylene (PTFE), nylon-6, nylon-12, polyethylene, and polypropylene are widely used. In the field of cosmetics, solid cosmetic compositions produced by compression molding differ from other fluid formulations in that solid powder raw materials account for a high content of approximately 70 to 90% of the total formulation. Accordingly, various microplastics are widely used to complement the formulation and feel, in addition to the main mineral powder raw materials.
[0003] These microplastics are released into the atmosphere and oceans after use, causing adverse effects on the environment and ecosystems as a whole, and can also cause health problems for humans through respiration or ingestion. In particular, microplastics, which are relatively small particles of about 10 μm or less, can damage the human immune and endocrine systems and have harmful effects such as exacerbating inflammatory responses and causing apoptosis of normal cells.
[0004] Accordingly, the inventors conducted research to develop a cosmetic composition that does not contain microplastics, and as a result, by using cellulose and a coated powder, they completed a cosmetic composition that does not contain microplastics while having excellent color development and usability. Prior art literature
[0005] (Patent Document 0001) KR 10-1845969 B The problem to be solved
[0006] The present invention aims to provide a cosmetic composition that does not contain microplastics and has excellent color development and usability.
[0007] The technical problems of the present invention are not limited to those mentioned above, and other unmentioned technical problems will be clearly understood by those skilled in the art from the description below. means of solving the problem
[0008] According to an embodiment of the present invention, a cosmetic composition is provided comprising cellulose and a powder surface-treated with at least one coating agent. The cosmetic composition is characterized by not containing microplastics.
[0009] In addition, the powder may contain magnesium / potassium / silicon / fluoride / hydroxide / oxide.
[0010] Additionally, the coating agent may comprise a first coating agent comprising isopropyl titanium triisostearate; and a second coating agent comprising a fatty acid or a fatty alcohol.
[0011] In addition, the cellulose may include spherical cellulose, and the average size of the spherical cellulose may be 10 to 17 μm.
[0012] In addition, the cellulose and the powder surface-treated with at least one coating agent may be included in a weight ratio of 1:0.5 to 7.
[0013] In addition, the coating agent may include a first coating agent comprising isopropyl titanium triisostearate; and a second coating agent comprising myristic acid.
[0014] In addition, the cosmetic composition may be in the form of a powder or compressed powder, and may be a color cosmetic composition. Effects of the invention
[0015] The present invention includes a powder surface-treated with cellulose and at least one coating agent, thereby ensuring sufficient stability and providing a suitable user experience. It can be provided to consumers as an eco-friendly cosmetic because it does not contain microplastics, which not only cause major environmental problems worldwide but also have adverse effects on consumers' health.
[0016] In addition, the cosmetic composition of the present invention provides excellent cosmetic effects comparable to the gloss and cosmetic effects exhibited by conventional cosmetic compositions containing microplastics, and also has the advantage of excellent usability, such as spreadability, adhesion, and longevity. Brief explanation of the drawing
[0017] A brief description of each drawing is provided to help to better understand the drawings cited in the detailed description of the invention. Figure 1 is a figure showing an SEM image of spherical cellulose included in one embodiment. Specific details for implementing the invention
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by a skilled expert in the art to which the present invention pertains. In general, the nomenclature used herein is well known and commonly used in the art. Furthermore, in describing embodiments of the present invention, detailed descriptions of related known components or functions are omitted if it is determined that such detailed descriptions would hinder understanding of the embodiments of the present invention. Additionally, while embodiments of the present invention will be described below, the technical concept of the present invention is not limited or restricted thereto and can be modified and implemented in various ways by those skilled in the art.
[0019] In this specification, when a part is described as including a certain component, it means that, unless specifically stated otherwise, it does not exclude other components but may include additional components. In this specification, the term "and / or" includes a combination of a plurality of related items or any one of a plurality of related items.
[0021] According to an embodiment of the present invention, a cosmetic composition comprising cellulose and a powder surface-treated with at least one coating agent is provided.
[0022] Cellulose is a polymeric compound in which D-glucose is linked in a straight chain shape by (1→4)-β-type glycosidic bonds, and refers to a lattice-type polysaccharide in which linear chains are overlapped. In the present invention, the cellulose can contribute to enhancing the user experience by strengthening the retention and texture of the product.
[0023] In the examples, spherical cellulose may be used instead of the general linear form of cellulose. The cosmetic composition of the present invention includes spherical cellulose to ensure sufficient stability while simultaneously achieving an appropriate texture and color development.
[0024] In one embodiment, the average size of the spherical cellulose may be 10 to 17 μm, specifically 12 to 15 μm. If the average size of the spherical cellulose is less than 10 μm, it may feel stiff and rough to use, and if the average size exceeds 17 μm, it may be difficult to form a cosmetic formulation due to excessive dusting and poor hardness and drop stability.
[0025] The size of the spherical cellulose refers to the largest diameter within the spherical cellulose, and the average size of the spherical cellulose refers to the average of the diameters of at least 90% of the spherical cellulose distributed in the composition, preferably by selecting spherical cellulose corresponding to 90% or more, 91% or more, 92% or more, 93% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, and calculating the average of the largest diameter values measured in each of these particles. However, it is not limited thereto.
[0026] In one embodiment, the cellulose may be included in an amount of 1 to 14 weight% based on the total weight of the cosmetic composition, specifically in an amount of 2 to 10 weight%, and more specifically in an amount of 3 to 8 weight%. If the cellulose is included in an amount of less than 1 weight% based on the total weight of the cosmetic composition, spreadability and the like may be poor, and it may not provide a sufficient cosmetic effect. If it is included in an amount exceeding 14 weight%, hardness may decrease, and drop stability and adhesion may also decrease. However, it is not limited thereto.
[0028] In the present invention, the powder may be surface-treated with at least one coating agent. As the powder of the present invention is surface-treated with at least one coating agent, it provides excellent water repellency and dispersibility, improves cosmetic durability, and can help with hardness and drop stability when contained in a solid compressed powder.
[0029] In one embodiment, the powder may include an inorganic powder or a composite silicon powder, and specifically, may include magnesium / potassium / silicon / fluoride / hydroxide / oxide. Magnesium / potassium / silicon / fluoride / hydroxide / oxide is a material obtained from potassium silicon fluoride and heated talc, and can be used as a substrate for coating.
[0030] In the present invention, the coating agent can influence the formation of hardness and the feel of use of the cosmetic composition finally manufactured by coating the powder that serves as the substrate. At least one type of coating agent may be used, and specifically, two or more types may be used. When the powder is surface-treated with two or more types of coating agents, dispersion stability, cosmetic durability, water repellency, and color development may be exhibited more excellently compared to when the coating agent is used alone.
[0031] In one embodiment, the coating agent may comprise a first coating agent comprising isopropyl titanium triisostearate; and a second coating agent comprising a fatty acid or a fatty alcohol.
[0032] The first coating agent comprises isopropyl titanium triisostearate. The isopropyl titanium triisostearate has the advantage of providing excellent spreadability, similar to a cream, when coated onto a powder.
[0033] The second coating agent may include a fatty acid or a fatty alcohol. When additional surface treatment is performed with the second coating agent, dispersion stability, cosmetic durability, etc., can be sufficiently improved compared to when the first coating agent (isopropyl titanium triisostearate) is coated alone.
[0034] In one embodiment, the fatty acid may be one or more selected from the group consisting of myristic acid, lauric acid, palmitic acid, stearic acid, behenic acid, caproic acid, linoleic acid, oleic acid, and isostearic acid, and preferably may be myristic acid, but is not limited thereto.
[0035] In one embodiment, the fatty alcohol may be one or more selected from the group consisting of myristyl alcohol, lauryl alcohol, cetyl alcohol, stearyl alcohol, behenyl alcohol, palmityl alcohol, linoleyl alcohol, oleyl alcohol, and isostearyl alcohol, and preferably may be myristyl alcohol, but is not limited thereto.
[0036] In one embodiment, the powder may be MAGNESIUM / POTASSIUM / SILICON / FLUORIDE / HYDROXIDE / OXIDE*ISOPROPYL TITANIUM TRIISOSTEARATE*MYRISTIC ACID. This is a surface treatment of the plate-shaped powder containing magnesium / potassium / silicon / fluoride / hydroxide / oxide elements with isopropyltitanium triisostearate and myristic acid, which helps to form the hardness of the composition and can improve the feel of use.
[0037] In one embodiment, the powder may be a plate-shaped powder. This plate-shaped powder can be mixed and compressed with cellulose to form the basic framework of the formulation. By including spherical cellulose and coated plate-shaped powder as the basic framework constituting the formulation, the stability of the raw materials can be improved while simultaneously providing an excellent user experience.
[0038] In one embodiment, the powder surface-treated with at least one coating agent may be included in an amount of 3 to 30 weight% with respect to the total weight of the cosmetic composition, specifically 4 to 25 weight%, and more specifically 5 to 20 weight%. If the powder surface-treated with the coating agent is included in an amount of less than 3 weight%, cosmetic effects such as spreadability, adhesion, and durability may be significantly reduced, and if the powder surface-treated with the coating agent is included in an amount of more than 30 weight%, hardness and drop stability may decrease, and spreadability may also be poor. However, it is not limited thereto.
[0039] In one embodiment, the magnesium / potassium / silicon / fluoride / hydroxide / oxide may be included in an amount of 95 to 99 weight% with respect to the total weight of the powder surface-treated with at least one coating agent, preferably in an amount of 96 to 98 weight%. However, it is not limited thereto.
[0040] In one embodiment, the at least one coating agent may be included in an amount of 1 to 5 weight percent based on the total weight of the surface-treated powder, preferably in an amount of 2 to 4 weight percent. However, it is not limited thereto.
[0042] In one embodiment, the drop stability, hardness, spreadability, adhesion, powder scattering, durability, etc. of the cosmetic composition may vary depending on the weight ratio of the cellulose and at least one coating agent surface-treated powder in the cosmetic composition.
[0043] Specifically, the cellulose and the powder surface-treated with at least one coating agent may be included in a weight ratio of 1:0.5 to 7, specifically in a weight ratio of 1:0.5 to 5, and more specifically in a weight ratio of 1:1 to 4. If the weight ratio of the cellulose and the powder surface-treated with at least one coating agent is less than 1:0.5 (where the powder is included in an amount less than 0.5 weight parts based on 1 weight part of cellulose), spreadability, adhesion, and durability all decrease, and dust scattering may occur. If the weight ratio of the cellulose and the powder surface-treated with at least one coating agent exceeds 1:7 (where the powder is included in an amount exceeding 7 weight parts based on 1 weight part of cellulose), the hardness is low, making it unstable when dropped, spreadability is significantly reduced, and dust scattering occurs significantly, which may result in a poor user experience. However, this is not limited thereto.
[0045] The cosmetic composition of the present invention may not contain microplastics. Since the cosmetic composition of the present invention comprises cellulose and a powder surface-treated with at least one coating agent, it is possible to provide a cosmetic composition with excellent spreadability, adhesion, durability, and color without containing microplastics, which are a concern regarding stability. Therefore, it is possible to resolve environmental issues and concerns regarding instability associated with conventional cosmetic compositions containing microplastics.
[0046] In one embodiment, the cosmetic composition according to the present invention may additionally include ingredients found in general cosmetic compositions in addition to the above ingredients, such as colorants, pigments, fragrances, preservatives, functional ingredients, dispersants, moisture evaporation barriers, emulsifiers, ion chelating agents, disinfectants, pH adjusters, antioxidants, alcohols, plant extracts, fragrances, cooling agents, thickeners, oils, etc. The above colorant is a concept that includes extender pigments such as talc, mica, sericite, silica, calcium carbonate, kaolin, and starch, inorganic pigments such as metal iron oxides, organic pigments such as tar pigments, and pearlescent pigments utilizing the refractive index of the pigment. In one embodiment, the above dispersant may be a non-surfactant dispersant and may include silica*caprylic / capric triglyceride*methicone or caprylic / capric triglyceride. The above-mentioned thickening agent is also called a thickening stabilizer and may include octyldodecyl stearoyl stearate, sodium polyacrylate, dibutyl lauroyl glutamide, or dibutyl ethylhexanoyl glutamide. The above-mentioned moisture barrier is also called a moisturizer and provides moisture to the skin or maintains skin moisture and provides a continuous moisturizing sensation; it is preferably a water-soluble ingredient and may be phenyl trimethicone, dipentaerythrityl hexahydroxystearate / hexastearate / hexarosinate, glycerin, or butylene glycol. The above-mentioned emulsifier is a substance used to facilitate the preparation of the emulsion and maintain the stability of the resulting emulsion, and may be glyceryl caprylate / 1,2-hexanediol, laureth-4, or PEG-7 glyceryl cocoate. However, it is not limited thereto. The amounts of the ingredients described above are not particularly limited and can be easily selected by a person skilled in the art within a range that does not impair the purpose and effects of the present invention.
[0047] In one embodiment, the cosmetic composition may be in a solid form, specifically, a powder or compressed powder form. However, it is not limited thereto and may be in a stick or cake form. For example, it may be a stick makeup base, stick foundation, stick sun cream, two-way cake, face powder, compact, pact, powder blusher, stick blusher, powder eyeshadow, stick eyeshadow, lipstick, lip balm, etc., but is not limited thereto.
[0048] In one embodiment, the cosmetic composition may be a color cosmetic composition. The concept of a color cosmetic includes all cosmetic compositions used for correction and beautification, which are applied to a part of the body, mainly the face, to display color, conceal skin imperfections, and change skin color to provide a sense of depth and color, but is not limited thereto.
[0049] In one embodiment, the hardness of the cosmetic composition is 850 to 1450 gf / cm when measured with a rheometer. 2 It may be, preferably 900 to 1400 gf / cm 2 It may be. When measured with a rheometer, the hardness of the cosmetic composition is 850 gf / cm 2 If it is less than that, drop stability decreases, making it difficult to use as a cosmetic, and the hardness is 1450 gf / cm 2 If exceeded, it becomes too hard, resulting in reduced spreadability and adhesion, which may decrease usability. However, it is not limited to this.
[0051] In the following, examples and experimental examples are presented to further explain the present invention in more detail, but the present invention is not limited thereto.
[0053] Experimental Example 1. Comparative experiment according to cellulose content
[0054] (1) Preparation of Example 1 and Comparative Examples 1 to 3
[0055] For comparative experiments based on cellulose content, cosmetic compositions of the Examples and Comparative Examples were prepared according to the contents of Table 1 below. For the coating powder, magnesium / potassium / silicon / fluoride / hydroxide / oxide*isopropyltitanium triisostearate*myristic acid surface-treated with two types of coating agents was used, and spherical cellulose was used for the cellulose. The unit of the contents in Table 1 is weight%.
[0056]
[0057] The specific manufacturing method is as follows.
[0058] First, to prepare a powder surface-treated with a coating agent, 97 parts by weight of magnesium / potassium / silicon / fluoride / hydroxide / oxide, 2 parts by weight of isopropyl titanium triisostearate, and 1 part by weight of myristic acid were mixed, ground and mixed using a Henschel mixer at 500 to 1000 RPM for 1 to 5 minutes, and then dried for 3 to 6 hours. Accordingly, a coated powder with a particle size of 0.01 to 50 μm was obtained. The particle size of the coated powder can be adjusted according to the application of the powder in cosmetics.
[0059] Next, a cosmetic composition was prepared with the ingredients and content of Table 1. Specifically, the extender pigment and colorant were added to a Henschel mixer and mixed at high speed (1,500–1,700 rpm). Subsequently, an oil binder heated to 75°C was added and mixed at high speed (1,500–1,700 rpm) to finally complete the cosmetic composition of Example 1.
[0060] Comparative Examples 1 to 3 were prepared by preparing a cosmetic composition in the same manner as Example 1, but with different cellulose content.
[0062] (2) Drop stability evaluation
[0063] Drop stability was measured to determine the molding stability of the cosmetic compositions of Example 1 and Comparative Examples 1 to 3. Specifically, drop stability was measured by vertically dropping the molded product three times from a height of 50 cm onto a 1 mm wooden board. If no breakage occurred in the formulation after the drop, it was evaluated as stable, and if breakage occurred in the contents, it was evaluated as unstable. The evaluation results are summarized in Table 2 below.
[0065] (3) Hardness measurement
[0066] Hardness was measured to determine the molding stability of the cosmetic compositions of Example 1 and Comparative Examples 1 to 3. Specifically, the surface of the molded product was measured using a rheometer, and the average of three measurements was calculated and presented (Unit: gf / cm²). 2 The measurement results are summarized in Table 2 below.
[0068] (4) Sensory evaluation
[0069] A sensory evaluation was performed to assess the usability of the cosmetic compositions of Example 1 and Comparative Examples 1 to 3. Specifically, 10 subjects with an average age of 20 to 30 were selected, and after applying the cosmetic compositions to their arms, a sensory evaluation was conducted regarding the spreadability, adhesion, and powder scattering felt upon application to the skin. The measurement results are summarized in Table 2 below. The results of the sensory evaluation regarding spreadability, adhesion, powder scattering, and durability were presented based on a 5-point scale (5: Very Good, 4: Slightly Good, 3: Average, 2: Slightly Poor, 1: Very Poor). In this case, regarding powder scattering, a lower score was indicated as more powder was scattered.
[0070]
[0071] As can be seen in Table 2 above, in the case of Example 1, which contains 5% by weight of cellulose relative to the total cosmetic composition, it has a sufficient level of hardness as a solid cosmetic composition, excellent spreadability and adhesion, does not cause much powder scattering, and also has excellent durability when applied to the skin.
[0072] On the other hand, Comparative Example 1, which does not contain cellulose, showed poor molding stability due to very low drop stability and hardness. Comparative Example 2, which contains 0.1% by weight of cellulose relative to the total composition, showed relatively stable molding stability, but it was found that spreadability and adhesion were poor, powder was flying around excessively, and durability was also poor. Comparative Example 3, which contains 15% by weight of cellulose relative to the total composition, showed not only insufficient hardness but also significantly reduced adhesion, powder flying around, and poor durability. Through this, it was confirmed that cellulose is an important factor in improving molding stability, usability, and cosmetic effects, and it is necessary to appropriately control the content of cellulose included in solid cosmetic compositions.
[0074] Experimental Example 2. Comparative experiment based on the content of powder surface-treated with two types of coating agents
[0075] (1) Preparation of Examples 2 to 3 and Comparative Examples 4 to 7
[0076] Examples 2 and 3, and Comparative Examples 4 to 7 were prepared by preparing cosmetic compositions in the same manner as in the examples, but with different amounts of magnesium / potassium / silicon / fluoride / hydroxide / oxide*isopropyltitanium triisostearate*myristic acid, which are powders surface-treated with two types of coating agents. The specific amounts are as shown in Table 3 below, and the unit of the ingredient amounts in Table 3 is weight%. The remaining ingredients and amounts are the same as in Example 1, and Example 1 is listed together for comparison.
[0077]
[0079] (2) Drop stability, hardness and sensory evaluation
[0080] Drop stability and hardness were measured to determine the molding stability of the cosmetic compositions of Examples 2 and 3 and Comparative Examples 4 to 7, and sensory evaluations were performed to evaluate their usability. The method of execution and the method of displaying results were the same as those shown in Experimental Example 1 above, and the experimental results are shown in Table 4 below.
[0081]
[0082] As can be seen in Table 4 above, Examples 1 to 3, which contain magnesium / potassium / silicon / fluoride / hydroxide / oxide*isopropyltitanium triisostearate*myristic acid in an amount of 5 to 20 weight% relative to the total cosmetic composition, were found to be excellent in terms of spreadability, adhesion, dust scattering, drop stability, and hardness, thus confirming their excellence as cosmetic products. On the other hand, Comparative Examples 4 to 6, which contain coating powder in an amount of 2 weight% or less relative to the total composition or do not contain coating powder, showed that the hardness became too high, resulting in reduced spreadability and adhesion, excessive dust scattering, and reduced durability. Furthermore, Comparative Example 7, which contains coating powder in an amount of 40 weight% or more relative to the total composition, showed that the hardness was too low, it was unstable upon dropping, and it exhibited poor spreadability and severe dust scattering.
[0083] Through this, it has been confirmed that the coating powder of the present invention is an important factor in improving molding stability, usability, and cosmetic effects, and it is known that it is necessary to appropriately control the content of the coating powder included in the cosmetic composition. In addition, it can be seen that when the weight ratio of the powder surface-treated with two or more coating agents of the present invention and cellulose is within an appropriate range, molding stability, spreadability, and adhesion are improved.
[0085] Experimental Example 3. Comparative experiment with microplastics
[0086] (1) Preparation of Comparative Examples 8 to 11
[0087] Comparative Examples 8 to 11 were prepared by preparing cosmetic compositions in the same manner as in the Examples, but with various types of microplastics added instead of cellulose as a formulation agent. The specific contents are as shown in Table 5 below, and the unit of the ingredient contents in Table 5 is weight%. The remaining ingredients and contents are the same as in Example 1.
[0088]
[0090] (2) Drop stability, hardness and sensory evaluation
[0091] Drop stability and hardness were measured to determine the molding stability of the cosmetic compositions of Comparative Examples 8 to 11, and sensory evaluations were performed to evaluate their usability. The method of execution and the method of displaying results were the same as those shown in Experimental Example 1 above, and the experimental results are shown in Table 6 below.
[0092]
[0093] As can be seen in Table 6 above, Example 1, a cosmetic composition prepared without using microplastics, was found to have excellent molding stability, exhibiting drop stability and hardness similar to or higher than Comparative Examples 8 to 11 prepared with microplastics, and received higher evaluation scores in terms of spreadability, adhesion, powder scattering, and overall durability. Through this, it can be seen that the cosmetic composition of the present invention can be utilized as a cosmetic with excellent molding stability and spreadability without containing microplastics that cause environmental problems.
[0095] Foregoing, specific parts of the content of the present invention have been described in detail. It will be apparent to those skilled in the art that such specific descriptions are merely preferred embodiments and do not limit the scope of the present invention. Accordingly, the actual scope of the present invention is defined by the appended claims and their equivalents.
Claims
Claim 1 cellulose; and a powder surface-treated with a coating agent, wherein the coating agent comprises a first coating agent comprising isopropyl titanium triisostearate; A cosmetic composition comprising: a second coating agent comprising a fatty acid or a fatty alcohol; wherein the powder comprises magnesium / potassium / silicon / fluoride / hydroxide / oxide, the cellulose comprises 2 to 10 weight% based on the total weight of the cosmetic composition, the powder surface-treated with the coating agent comprises 5 to 20 weight% based on the total weight of the cosmetic composition, the fatty acid is one or more selected from the group consisting of myristic acid, lauric acid, palmitic acid, stearic acid, behenic acid, caproic acid, linoleic acid, oleic acid, and isostearic acid, and the fatty alcohol is one or more selected from the group consisting of myristyl alcohol, lauryl alcohol, cetyl alcohol, stearyl alcohol, behenyl alcohol, palmityl alcohol, linoleyl alcohol, oleyl alcohol, and isostearyl alcohol. Claim 2 delete Claim 3 delete Claim 4 A cosmetic composition according to claim 1, wherein the cosmetic composition does not contain microplastics. Claim 5 delete Claim 6 A cosmetic composition according to claim 1, wherein the cellulose comprises spherical cellulose, and the average size of the spherical cellulose is 10 to 17 μm. Claim 7 delete Claim 8 A cosmetic composition according to claim 1, wherein the cellulose and the powder surface-treated with the coating agent are included in a weight ratio of 1:0.5 to 7. Claim 9 delete Claim 10 delete Claim 11 A cosmetic composition according to claim 1, wherein the cosmetic composition is in the form of a powder or compressed powder.
Citation Information
Patent Citations
Powder cosmetic composition containing nanocrystalline cellulose
KR1020190090375A
Silicone-free coated powder for cosmetics and cosmetics comprising thereof
KR1020210046238A
Cosmetic composition with excellent tabletting properties and dropping stability
KR1020220080558A
Silica particles as substitutes of microplastic beads for cosmetics and cosmetic composition comprising the same
KR1020230093631A